2012
DOI: 10.1002/phar.1214
|View full text |Cite
|
Sign up to set email alerts
|

Process Indicators of Quality Clinical Pharmacy Services During Transitions of Care

Abstract: The American College of Clinical Pharmacy charged the Public and Professional Relations Committee to develop a short white paper describing quality measures of clinical pharmacists' patient care services in transitional care settings. Transitional care describes patient movement from one health care setting or service to another. Care transitions are associated with an increased risk of adverse events for patients. Pharmacists play an important role in ensuring that medication errors and adverse events are min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…Pharmacists in the community setting have the ability to resolve medication discrepancies, improve patient understanding of medications, and address adverse effects. 1,2,5 These factors can all affect a patient's adherence to medications and may be improved by pharmacist interventions in the post-discharge period.…”
Section: Innovations In Pharmacymentioning
confidence: 99%
See 2 more Smart Citations
“…Pharmacists in the community setting have the ability to resolve medication discrepancies, improve patient understanding of medications, and address adverse effects. 1,2,5 These factors can all affect a patient's adherence to medications and may be improved by pharmacist interventions in the post-discharge period.…”
Section: Innovations In Pharmacymentioning
confidence: 99%
“…Of those individuals readmitted, 76% were described as being potentially preventable, resulting in an additional $12 billion healthcare dollars spent. [2][3] In 2011, the Affordable Care Act established the Hospital Readmissions Reduction Program to reduce payments for hospitals with excess readmissions. This program focuses specifically on 30 day readmissions for acute myocardial infarction, heart failure, and pneumonia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transition from home to hospital is a high source of medication errors, which emphasizes the importance of medication reconciliation at hospital admission. 24 Medication reconciliation is also one of the primary interventions made at discharge to identify changes in regimens and reduce errors; however, evidence shows that room for improvement exists in this area as medication errors are still prevalent, and patients do not always understand their regimens. A prospective study of 377 elderly patients discharged with hF, ACS, or pneumonia found that more than 80% of patients experienced a prescribing error at discharge or did not comprehend at least one of their medication changes at discharge.…”
Section: Medication Reconciliationmentioning
confidence: 99%
“…2 The National Transitions of Care Coalition (NTOCC) also endorsed the use of pharmacists in the care plan, including medication reconciliation, medication management sessions, comprehensive medication counseling, assessment of patient and caregiver understanding, and telephonic follow-up. 3 Finally, the American Society of HealthSystem Pharmacists (ASHP) and American Pharmacists Association (APhA) published a best practices paper that provided profiles for 8 successful programs as part of the Medication Management in Care Transitions (MMTC) project.…”
mentioning
confidence: 99%